Effect of minidose aspirin on renal function and renal uric acid handling in healthy young adults - Louthrenoo W. (2014)
Minidose aspirin (60-325 mg/day) has been widely used in the prevention and treatment of cardiovascular and cerebrovascular diseases. However, studies on the effects of minidose aspirin on renal handling of uric acid and renal function are limited. We studied the effect of aspirin at 60 mg/day (n = 18) and 300 mg/day (n = 14) on uric acid handling and renal function in healthy subjects. The subjects were evaluated weekly during 2 weeks of aspirin therapy, and again 1 week after aspirin was discontinued. Aspirin at both dosages decreased the fractional excretion of uric acid. However, aspirin at 300 mg/day, but not 60 mg/day, significantly decreased uric acid clearance and creatinine clearance by the end of the second week of aspirin therapy. Despite these changes, serum uric acid and serum creatinine remained constant. The uric acid clearance, but not the creatinine clearance, returned to baseline value 1 week after aspirin therapy was discontinued. As aspirin at 60 mg/day showed no suppressive effect on renal function, it may be better for long-term use.